Service quality gaps and their role in service enterprises development - Wiesław Urban (Technological and Economic Development of Economy, 2009)
The study takes into consideration the problem of organizational quality gaps where the quality losses occur. Many service quality gaps are reviewed in this paper. But the four out of five quality gaps by Parasuraman et al.(1985) are examined. The main management problem, according to research achievements, is the gap between managers’ perception of customers’ expectation and service specifications existing in organizations. In a service organization usually more quality gaps might be identified. Identification of specific quality gaps is advantageous from a management point of view.